2018
DOI: 10.1016/j.fluid.2018.05.025
|View full text |Cite
|
Sign up to set email alerts
|

The unavoidable necessity of considering temperature dependence of the liquid Gibbs energy of mixing for certain VLE data correlations

Abstract: The unavoidable necessity of considering temperature dependence of the liquid Gibbs energy of mixing for certain VLE data correlations,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…In a previous paper [6], we achieved similar conclusions for temperature, demonstrating that for some isobaric VLE data sets, the use of additional T-dependence, like the one represented in Eqs. ( 1) and (2), is not a question of increasing the flexibility of the model because of the higher number of parameters used, but is demanded by the VLE data set itself.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 77%
See 4 more Smart Citations
“…In a previous paper [6], we achieved similar conclusions for temperature, demonstrating that for some isobaric VLE data sets, the use of additional T-dependence, like the one represented in Eqs. ( 1) and (2), is not a question of increasing the flexibility of the model because of the higher number of parameters used, but is demanded by the VLE data set itself.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 77%
“…There are a considerable number of VLE data sets, both isobaric and isothermal, with a very standard appearance that inexplicably cannot be satisfactorily correlated with any of the existing models to formulate the non-idealities of the liquid mixtures. From the point of view presented in this paper for isothermal conditions, and in a previous paper [6] for isobaric conditions, we have demonstrated that for these systems no model, as highly flexible as can be imagined, can fit the data if P or T dependence, respectively, are not included in the parameters of the model.…”
Section: Procedures For the Correlation Of Vle Datamentioning
confidence: 62%
See 3 more Smart Citations